Prepreg, fiber-reinforced composite material, and method for producing fiber-reinforced composite material

By integrating thermoplastic resin particles with low glass transition temperatures and an epoxy resin composition, the fiber-reinforced composite materials achieve improved impact resistance and reduced delamination, enhancing their durability and structural integrity.

JP7616076B2Active Publication Date: 2025-01-17MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021567613
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2020-12-24
Publication Date
2025-01-17
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

Fiber-reinforced composite materials face issues with insufficient impact resistance due to stress concentration in the interlayer regions, leading to delamination and poor performance under external impacts.

Method used

Incorporating thermoplastic resin particles with low glass transition temperatures and uneven distribution on the surface of prepregs, along with an epoxy resin composition, to enhance the interlayer bonding and absorb impact energy, thereby reducing delamination.

Benefits of technology

The resulting composite materials exhibit improved resistance to point impacts and maintain structural integrity by minimizing delamination, offering enhanced durability and impact durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616076000001
    Figure 0007616076000001
Patent Text Reader

Abstract

Provided are: a prepreg that makes it possible to produce a fiber-reinforced composite material in which peeling between layers at a point impact is suppressed; a fiber-reinforced composite material having excellent durability against a point impact; and a method for manufacturing said fiber-reinforced composite material. The projection area of a damaged part of a cured article, obtained by curing a prepreg according to the present invention under a specific curing condition, is 400 mm2 or less, when the projection area is measured by a specific test 1. The maximum value of tanδ of the cured product, when the tanδ is measured by a specific test 2, is observed at 100°C or higher. The prepreg contains a fiber-reinforced base material, an epoxy resin composition, and a polymer (C2), where the polymer (C2) is present on the outermost surface of the prepreg, and the polymer (C2) is observed to have a glass transition temperature of 10°C or lower under a specific measurement condition. A fiber-reinforced composite material production method according to the present invention includes thermoforming of the prepreg according to the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a prepreg, a fiber-reinforced composite material, and a method for producing a fiber-reinforced composite material. This application claims priority based on Japanese Patent Application No. 2019-237641, filed on December 27, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] Fiber-reinforced composite materials are lightweight and have high strength and rigidity, and therefore are widely used in the fields of sports, leisure, automobiles, aircraft, other general industries, etc. Recently, fiber-reinforced composite materials that are particularly lightweight, high strength, and high rigidity have been used in the fields of automobiles, aircraft, etc.

[0003] Fiber-reinforced composite materials are materials composed of reinforcing fibers and a matrix resin. They are anisotropic materials that exhibit extremely high strength and elastic modulus against stress applied along the fiber axis of the reinforcing fibers, but exhibit low strength and elastic modulus against stress applied perpendicular to the fiber axis.

[0004] Fiber-reinforced composite materials are produced, for example, by laminating prepregs impregnated with an uncured thermosetting resin composition onto a reinforcing fiber substrate, molding the laminate, and then heating and curing the thermosetting resin composition. In producing the fiber-reinforced composite material, the physical properties in each direction of the fiber-reinforced composite material can be controlled by using a prepreg in which a woven reinforcing fiber fabric is used as the reinforcing fiber substrate, or by laminating multiple prepregs in which reinforcing fibers aligned in one direction are used as the reinforcing fiber substrate, with the fiber axes oriented in different directions.

[0005] However, in fiber-reinforced composite materials manufactured by laminating multiple prepregs, the proportion of reinforcing fibers in the interlayer region, which mainly contains the matrix resin, near the surface of the laminated prepregs may be small, and the orientation of the reinforcing fibers on both sides of the interlayer region may be different from each other. Therefore, when an external impact is applied, stress is particularly concentrated in the interlayer region of the fiber-reinforced composite material. Failure in this interlayer region can be the initiation point for total failure of the fiber-reinforced composite material. Therefore, even if the strength of the reinforcing fibers is improved, unless the fracture in the interlayer region is suppressed, dynamic mechanical strength, particularly resistance to external impact, cannot be drastically improved. To solve this problem, methods have been proposed in which various particles, including thermoplastic resins, are unevenly distributed between the layers (for example, Patent Documents 1 and 2). Patent Document 1 discloses a prepreg in which core / shell rubber particles are arranged on the surface layer of the prepreg. By using a soft rubber for the core and a hard resin for the shell, the core / shell rubber can be prevented from dissolving in the epoxy resin. The use of this core / shell rubber can prevent differences in the degree of interlayer morphology formation due to differences in curing conditions and the resulting fluctuations in impact resistance. Furthermore, Patent Document 2 discloses a prepreg in which two types of particles with different particle diameters, each having a glass transition temperature of 80° C. or higher, are arranged on the surface layer of the prepreg. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 9-25393 [Patent Document 2] Japanese Patent Application Laid-Open No. 2014-145003 Summary of the Invention [Problem to be solved by the invention]

[0007] Laminates using interlayer reinforcing particles may not have sufficient resistance to point impacts when a resin with a high elastic modulus is used as the shell of core / shell structured particles, as in the examples of Patent Document 1, or when particles with a high glass transition temperature are used, as in the examples of Patent Document 2. In other words, the reinforcing particles do not absorb the impact energy, and cracks propagate widely in the fiber direction at the interface between the particles and the particularly fragile matrix resin in the laminate, completely separating the interface between the particles and the matrix, causing the particles to peel off, which may actually worsen the impact resistance.

[0008] The present invention provides a prepreg from which a fiber-reinforced composite material in which interlayer delamination upon point impact is suppressed; a fiber-reinforced composite material that is excellent in resistance to point impact; and a method for producing the same. [Means for solving the problem]

[0009] One embodiment of the present invention relates to the following [1] to

[20] . [1] A prepreg, wherein the projected area of ​​a damaged portion of a cured product obtained by curing the prepreg under the following curing conditions is 400 mm2 or less, as measured by the following test 1: 2 or less, and the maximum value of tan δ of the cured product measured by the following Test 2 is observed at 100°C or higher. Curing conditions: The prepreg is laminated in a "+45 / 0 / -45 / 90" 4s configuration and cured in an autoclave at 0.6 MPa and 150°C for 30 minutes. Test 1: A panel made of the cured product is placed, and an iron impactor with a hemisphere of radius 8 mm attached to the tip is dropped onto the center of the panel with a potential energy of 26 J. The damaged area on the panel caused by the drop is detected using a transmission type ultrasonic flaw detector with a sound pressure of 22 dB, and the area of ​​the detected damaged area is measured and used as the projected area of ​​the damaged area. Test 2: Using a dynamic viscoelasticity measuring device, the storage modulus E' and loss modulus E'' were measured under the conditions of a frequency of 1 Hz, a heating rate of 5°C / min, and a measurement temperature range of 30°C to 250°C. The ratio of the loss modulus E'' to the storage modulus E' (E'' / E') was defined as tan δ. [2] The prepreg according to [1], comprising the following components (A), (B), and (C): Component (A): Reinforced fiber substrate Component (B): Epoxy resin composition Component (C): Particle [3] The prepreg according to [2], wherein the component (C) is present on the outermost surface of the prepreg. [4] The prepreg according to [2] or [3], wherein the component (C) is thermoplastic resin particles. [5] The prepreg according to any one of [2] to [4], wherein the component (C) is a particle containing a polyacrylic acid ester. [6] The prepreg according to any one of [2] to [5], wherein the component (C) is crosslinked particles of a polyacrylic acid ester. [7] The prepreg according to any one of [2] to [6], wherein the median (D50) of the particle size distribution of the particles of the component (C) is 12 μm or more and 21 μm or less. [8] The prepreg according to any one of [2] to [7], wherein the component (B) contains dicyandiamide. [9] The prepreg according to any one of [2] to [8], wherein the component (B) contains an epoxy resin, and the glass transition temperature of a cured product of the epoxy resin is −20° C. or lower.

[10] The prepreg according to any one of [2] to [9], wherein the component (A) is a carbon fiber substrate.

[11] A fiber-reinforced composite material obtained by laminating at least one sheet of the prepreg according to any one of [1] to

[10] and another prepreg.

[12] A prepreg comprising the following components (A), (B), and (C2), wherein the component (C2) is present on the outermost surface of the prepreg: Component (A): Reinforced fiber substrate Component (B): Epoxy resin composition Component (C2): A polymer having a glass transition temperature of 10°C or less observed under the following measurement conditions: Measurement conditions for the glass transition temperature of component (C2): The prepreg was cut into 100 mm x 100 mm pieces and washed with 50 ml of NMP (N-methylpyrrolidone), after which the washings were filtered through filter paper. This process was repeated five times using the same filter paper, after which the filter paper was washed with acetone and dried in an oven at 100°C for 30 minutes. 5 to 10 mg of residue was removed from the filter paper and scanned by differential scanning calorimetry (DSC) from -50°C to 300°C at 10°C / min. The onset value at which the baseline changed was taken as the glass transition temperature.

[13] The prepreg according to

[12] , wherein the component (C2) contains a polyacrylic acid ester.

[14] The prepreg according to

[12] or

[13] , wherein the component (C2) is a particle, and the particle is unevenly distributed on the outermost surface of the prepreg.

[15] The prepreg according to any one of

[12] to

[14] , wherein the component (C2) is a crosslinked particle.

[16] The prepreg according to any one of

[12] to

[15] , wherein the component (A) is a carbon fiber substrate.

[17] The prepreg according to any one of

[12] to

[16] , which is for a tubular body.

[18] A tubular body obtained by curing the prepreg according to any one of

[12] to

[16] .

[19] A method for producing a fiber-reinforced composite material, comprising hot molding a prepreg containing the following components (A), (B), and (C2) at 100°C or higher and 150°C or lower: Component (A): Reinforced fiber substrate Component (B): Epoxy resin Component (C2): A polymer having a glass transition temperature of 10°C or less observed under the following measurement conditions: Measurement conditions for the glass transition temperature of component (C2): The prepreg was cut into 100 mm x 100 mm pieces and washed with 50 ml of NMP (N-methylpyrrolidone), after which the washings were filtered through filter paper. This process was repeated five times using the same filter paper, after which the filter paper was washed with acetone and dried in an oven at 100°C for 30 minutes. 5 to 10 mg of residue was removed from the filter paper and scanned by differential scanning calorimetry (DSC) from -50°C to 300°C at 10°C / min. The onset value at which the baseline changed was taken as the glass transition temperature.

[20] The method for producing a fiber-reinforced composite material according to

[19] , wherein the prepreg is molded by internal pressure molding, autoclave molding, or press molding. [Effects of the Invention]

[0010] According to the present invention, it is possible to provide a novel fiber-reinforced composite material that has sufficient heat resistance as a fiber-reinforced composite material and also has excellent durability against impact, as well as a prepreg for producing the fiber-reinforced composite material and the fiber-reinforced composite material. DETAILED DESCRIPTION OF THE INVENTION

[0011] Hereinafter, a prepreg, a fiber-reinforced composite material, and a method for producing the same according to one embodiment of the present invention will be described in more detail.

[0012] The following definitions of terms apply throughout the specification and claims. The term "fiber reinforced composite material" refers to a material obtained by laminating prepregs and then reacting and curing or solidifying the resin components by heating or the like. The term "epoxy resin" refers to a compound having a glycidyl group in the molecule, or a resin having a glycidyl group. The term "thermoplastic resin" refers to a resin that softens at or above its glass transition temperature or melting point. The "glass transition temperature" is the onset value of the storage modulus E' determined by bending mode DMA in accordance with ASTM D7028. The symbol "to" indicating a range of values ​​means that the values ​​before and after it are included as the lower and upper limits.

[0013] <Prepreg> In one embodiment of the prepreg, the prepreg is cured under the following curing conditions, and the projected area of ​​the damaged portion measured by the following test 1 of the cured product is 400 mm 2 or less, and the maximum value of tan δ of the cured product measured by the following Test 2 is observed at 100° C. or higher. Curing conditions: The prepreg is laminated in a "+45 / 0 / -45 / 90" 4s configuration and cured in an autoclave at 0.6 MPa and 150°C for 30 minutes. Test 1: A panel made of the cured product obtained under the above curing conditions was placed, and an iron impactor with a hemisphere of radius 8 mm attached to the tip was dropped onto the center of the panel with a potential energy of 26 J. The damaged area on the panel caused by the drop was detected using a transmission type ultrasonic flaw detector with a sound pressure of 22 dB, and the area of ​​the detected damaged area was measured and used as the projected area of ​​the damaged area. Test 2: Using a dynamic viscoelasticity measuring device, measure the storage modulus E' and loss modulus E'' under the conditions of a frequency of 1 Hz, a heating rate of 5°C / min, and a measurement temperature range of 30°C to 250°C. Observe the temperature at which the ratio of storage modulus E' to loss modulus E'' (E'' / E' = tan δ) is maximized.

[0014] From the viewpoint of resistance to point impact, the prepreg preferably contains the following constituent elements (A), (B), and (C). Component (A): Reinforced fiber substrate Component (B): Epoxy resin composition Component (C): Particle

[0015] In a prepreg according to one embodiment, the prepreg includes the following constituent elements (A), (B), and (C2), with the constituent element (C2) being present on the outermost surface of the prepreg. Component (A): Reinforced fiber substrate Component (B): Epoxy resin composition Component (C2): A polymer having a glass transition temperature of 10°C or less observed under the following measurement conditions: Glass transition temperature measurement conditions: The prepreg was cut into 100mm x 100mm pieces and washed with 50ml of NMP (N-methylpyrrolidone), after which the washings were filtered through filter paper. This process was repeated five times using the same filter paper, after which the filter paper was washed with acetone and dried in a 100°C oven for 30 minutes. 5-10mg of residue was removed from the filter paper and scanned by differential scanning calorimetry (DSC) from -50°C to 300°C at 10°C / min. The onset value at which the baseline changed was taken as the glass transition temperature.

[0016] The projected area S of the damaged area determined by Test 1 is 400 mm 2 From the viewpoint of usability as a structural member of a moving body, the projected area S is 350 mm 2 Less than 300mm is preferable 2 The following is more preferable: From the viewpoint of maintaining the rigidity required for the structural members of the moving body, the projected area S is 20 mm 2 More than 50mm is preferable. 2 The above is more preferable. The value of this projected area S can also be said to be an index of the impact resistance of the component (C) or the component (C2). If the projected area S is small, when an object collides with the fiber-reinforced composite material, the kinetic energy of the object is converted into particle deformation energy in the fiber-reinforced composite material and is more likely to return to restoring energy. For example, the use of a fiber-reinforced composite material obtained from prepreg in bats, rackets, etc. is thought to contribute to improving the flight distance of the ball and realizing a soft feel when hit.

[0017] As the constituent elements (C) and (C2), it is preferable to use particles having a low Tg (glass transition temperature) and a low modulus of elasticity, such as crosslinked polyacrylates and block copolymers of different polyamides. Furthermore, polyamides that have been subjected to a hydrophilic surface treatment can also be used to suppress the interfacial propagation of cracks. When component (C) is used, the value of S can be reduced by using particles with a low Tg and a low elastic modulus, or by using polyamides that have been subjected to a hydrophilic surface treatment, and adding an epoxy resin having a component exhibiting rubber elasticity to component (B).

[0018] When component (A) is impregnated with component (B) and component (C) or component (C2), component (C) or component (C2) is filtered out by (A), and component (C) or component (C2) can be unevenly distributed on the prepreg surface. Multiple prepregs are laminated and cured, and the surface perpendicular to the fiber direction is polished. If particles or fused particles are observed between the prepreg layers, it can be said that component (C) or component (C2) is present on the surface of the prepreg. By molding a laminate in which prepregs in which component (C) or component (C2) are unevenly distributed on the surface of component (A) and component (A) are impregnated with component (B) and a portion of component (C) or component (C2), a fiber-reinforced composite material in which component (C) or component (C2) is unevenly distributed between the prepreg layers can be obtained. As a result, the fiber-reinforced composite material can be endowed with excellent resistance to point impacts. For example, the fiber-reinforced composite material is particularly preferably used as a tubular body, since it improves the coefficient of restitution of sports equipment.

[0019] (Curing conditions) The prepreg was cut into a 350mm x 350mm piece and laminated in a "+45 / 0 / -45 / 90" configuration to produce a 4-6mm thick prepreg laminate. The prepreg laminate was covered with nylon film and vacuum-bagged. It was then heated in an autoclave from room temperature to 150°C at a heating rate of 4°C / min and maintained at 150°C for 20 minutes. The prepreg laminate was then slowly cooled in the autoclave to 50°C or below to produce a molded plate for evaluation made from the cured prepreg. The pressure inside the autoclave was maintained at 0.6 MPa from the start to the end of heating.

[0020] (Test 1) A 150mm x 100mm test piece is cut from the evaluation molded plate and a diagonal line is drawn on the surface of the test piece. The test piece is placed stationary in an instrumented impact testing machine so that the intersection of the diagonal lines drawn on the test piece is directly below the impactor. An iron impactor with an 8mm radius hemisphere at its tip is set to a potential energy of 26J and the iron impactor is dropped onto the center of the test piece. The test piece is placed stationary in a water tank and ultrasonic waves at a sound pressure of 22dB are irradiated onto the test surface, and damaged areas are detected using the transmission method. The damaged area is projected and its area is measured, which is taken as the projected area S of the damaged area.

[0021] (tanδ) For the cured product of the prepreg cured under the above curing conditions, the maximum value of tan δ measured by the following Test 2 is observed at 100°C or higher. From the viewpoint of usability as a structural member for a mobile body, the temperature at which the maximum value of tan δ is observed is preferably 110°C or higher, and more preferably 120°C or higher. From the viewpoint of achieving both heat resistance and impact resistance, the temperature is preferably 200°C or lower, and more preferably 180°C or lower.

[0022] (Test 2) Using a dynamic viscoelasticity measuring device, the storage modulus E' and loss modulus E'' are measured under the conditions of a frequency of 1 Hz, a heating rate of 5°C / min, and a measurement temperature range of 30°C to 250°C. The temperature at which the ratio of storage modulus E' to loss modulus E'' (E'' / E' = tan δ) is maximized is observed. When measuring tan δ of a cured product, if multiple peaks of tan δ are observed, the temperature of the peak with the larger tan δ value is identified as the temperature at which the maximum tan δ is observed.If multiple peaks with the same value are observed, the temperature of the lower peak is identified as the temperature at which the maximum tan δ is observed.

[0023] The glass transition temperature of the cured prepreg is preferably 90°C or higher. From the viewpoint of usability as a structural member for a mobile object, it is more preferably 100°C or higher, and even more preferably 110°C or higher. From the viewpoint of compatibility with impact resistance, it is preferably 190°C or lower, and more preferably 170°C or lower. The glass transition temperature of the cured prepreg can be the onset value of the storage modulus E' determined by bending mode DMA in accordance with ASTM D7028.

[0024] (Component (A)) The component (A) is a reinforcing fiber substrate, and the reinforcing fiber substrate may have reinforcing fibers aligned in a single direction or in random directions. The component (A) may take the form of a woven fabric or nonwoven fabric of reinforcing fibers, or a sheet in which long reinforcing fibers are aligned in one direction.

[0025] From the viewpoint of being able to mold a fiber-reinforced composite material having high specific strength and specific modulus, the component (A) is preferably a sheet made of a bundle of reinforcing fibers in which long fibers are aligned in a single direction, and from the viewpoint of ease of handling, the component (A) is preferably a woven fabric of reinforcing fibers.

[0026] The reinforcing fibers may be long fibers, or the long fibers may be in the form of strands. The reinforcing fibers may be milled (milled reinforcing fibers), or the long fibers or their strands may be chopped (chopped reinforcing fibers).

[0027] Examples of materials for the reinforcing fibers include glass fibers, carbon fibers (including graphite fibers), aramid fibers, boron fibers, etc. From the viewpoints of mechanical properties and weight reduction of the fiber-reinforced composite material, the reinforcing fiber substrate is preferably a carbon fiber substrate.

[0028] The tensile strength of the carbon fiber according to JIS (Japanese Industrial Standards) R 7601 is preferably 3500 MPa or more, more preferably 4000 MPa or more, and even more preferably 4500 MPa or more.

[0029] For example, as a structural material for aircraft, the carbon fiber used in the fiber-reinforced composite material preferably has high tensile strength, and the tensile strength of the carbon fiber in accordance with JIS R 7601 is preferably 4500 MPa or more, more preferably 5000 MPa or more, and even more preferably 5500 MPa or more.

[0030] The fiber diameter of the carbon fibers is preferably 4 μm or more, more preferably 5 μm or more. Furthermore, the fiber diameter of the carbon fibers is preferably 10 μm or less, more preferably 8 μm or less. If the fiber diameter of the carbon fibers is 4 μm or more, the carbon fibers are less likely to break or become lint-filled when they rub against each other or against the surface of a roll as they move laterally during processes such as combing and rolling to process the carbon fibers. This makes it possible to suitably produce fiber-reinforced composite materials with stable strength. Furthermore, if the fiber diameter of the carbon fibers is 10 μm or less, carbon fibers can be produced by a conventional method. The number of carbon fibers in the carbon fiber bundle is preferably 1,000 to 60,000.

[0031] (Component (B)) Component (B) is an epoxy resin composition. It preferably contains a resin that constitutes the matrix of the fiber-reinforced composite material and a curing agent. The epoxy resin composition preferably contains an epoxy resin as the resin that constitutes the matrix, and dicyandiamide and / or a urea compound as the curing agent. Component (B) may further contain other components in addition to the epoxy resin and the curing agent.

[0032] Any epoxy resin can be used as the epoxy resin, including, for example, bisphenol A epoxy resin, bisphenol F epoxy resin, epoxy resin having an oxazolidone ring skeleton, novolac epoxy resin, triglycidylaminophenol, tetraglycidyldiaminodiphenylmethane, hydrophthalic acid epoxy resin, bisphenol S epoxy resin, resorcinol epoxy resin, hydroquinone epoxy resin, bisphenoxyethanol fluorene epoxy resin, bisphenol fluorene epoxy resin, and biscresol fluorene epoxy resin. Among these, one or more epoxy resins selected from the group consisting of bisphenol A epoxy resins, bisphenol F epoxy resins, epoxy resins having an oxazolidone ring skeleton, novolac epoxy resins, triglycidylaminophenol, and tetraglycidyldiaminodiphenylmethane are preferred. Liquid and solid epoxy resins can also be used in combination. From the viewpoint of improving the toughness of the cured product of component (B), bisphenol A epoxy resins are preferred.

[0033] Liquid epoxy resins are epoxy resins that are liquid at 25°C. Liquid epoxy resins primarily contribute to improving the solubility of thermoplastic resins and improving the strength, elastic modulus, and heat resistance of the cured product of the epoxy resin composition. Here, "liquid" means that the epoxy resin exhibits fluidity. The viscosity of the epoxy resin that is liquid at 25°C is preferably 500 Pa·s or less, more preferably 300 Pa·s or less, and more preferably 0.1 Pa·s or more at 25°C. Commercially available bisphenol A epoxy resins that are liquid at 25°C include, for example, jER (registered trademark) 828 from Mitsubishi Chemical, DER331 from Dow Chemical, Epotohto YD-128 from Nippon Steel Chemical & Material, and EPICLON 850 from DIC. Commercially available bisphenol A epoxy resins that are solid at 25°C include, for example, jER (registered trademark) 1001, jER (registered trademark) 1002, jER (registered trademark) 1003, and jER (registered trademark) 1004 from Mitsubishi Chemical Corporation, Epotohto YD-903 from Nippon Steel Chemical & Material Co., Ltd., and EPICLON 1050, EPICLON 2050, EPICLON 3050, and EPICLON 4050 from DIC.

[0034] For the purpose of further enhancing impact resistance, component (B) preferably contains an epoxy resin having an oxazolidone ring skeleton or an epoxy resin containing a skeleton exhibiting rubber elasticity in the main chain. The epoxy resin containing a skeleton exhibiting rubber elasticity in the main chain is preferably an epoxy resin having an ether bond and containing an alkylene structure, and a commercially available product thereof is, for example, YX7400 from Mitsubishi Chemical. Commercially available epoxy resins having an oxazolidone ring skeleton include EPICLON TSR-400 from DIC, Epotohto YD-952 from Nippon Steel Chemical & Materials, DER858 from Dow Chemical, and LSA3301 from Asahi Kasei E-materials. The content of the epoxy resin having an oxazolidone ring skeleton or the epoxy resin containing a skeleton exhibiting rubber elasticity in the main chain is preferably 1% by mass or more and 40% by mass or less, based on 100% by mass of the epoxy resin composition. The content of the epoxy resin in component (B) is preferably 60% by mass or more, more preferably 70% by mass or more, relative to 100% by mass of the epoxy resin composition. From the viewpoint of imparting sufficient impact resistance, the content is preferably 90% by mass or less, more preferably 80% by mass or less, relative to 100% by mass of the epoxy resin composition.

[0035] The curing agent is not particularly limited. Examples include dicyandiamide, urea compounds, imidazoles, aromatic amines, other amine-based curing agents, acid anhydrides, boron chloride amine complexes, etc. Among these, at least one curing agent selected from the group consisting of dicyandiamide, urea compounds, imidazoles, and aromatic amines is preferred. As the curing agent for the epoxy resin, dicyandiamide and urea compounds are preferred. By using dicyandiamide and urea compounds in combination, component (B) can be cured even at low temperatures of 150°C or less.

[0036] The content of dicyandiamide is preferably 3% by mass or more, and more preferably 4% by mass or more, based on 100% by mass of the epoxy resin composition. Furthermore, the content of dicyandiamide in component (B) is preferably 10% by mass or less, and more preferably 7% by mass or less, based on 100% by mass of the epoxy resin composition. When the content of dicyandiamide is 3% by mass or more, the epoxy resin can be sufficiently cured, and a cured product with higher heat resistance can be obtained. When the content of dicyandiamide is 10% by mass or less, stress concentration and moisture absorption caused by excess dicyandiamide can be suppressed, and a cured product with higher toughness and lower moisture absorption can be obtained. Commercially available dicyandiamide products include DICY7 and DICY15 from Mitsubishi Chemical Corporation, Dyhard (registered trademark) 100s from Alzchem, and DICYANEX 1400F from Air Products.

[0037] The urea compound contributes to promoting the reaction between the epoxy resin and dicyandiamide. As the urea compound, an aromatic urea compound is preferred from the viewpoint of improving the storage stability of the epoxy resin composition and improving the heat resistance of the cured product. Examples of the aromatic urea compound include N,N-dimethyl-N'-(3,4-dichlorophenyl)urea, toluenebis(dimethylurea), 4,4'-methylenebis(phenyldimethylurea), and 3-phenyl-1,1-dimethylurea. Commercially available aromatic urea compounds include DCMU99 from Hodogaya Chemical Co., Ltd., and Omicure® 24, Omicure® 52, and Omicure® 94 from PTI Japan. The content of the urea compound is preferably 0.5% by mass or more, and more preferably 1% by mass or more, relative to 100% by mass of the epoxy resin composition. The content of the urea compound is preferably 7% by mass or less, and more preferably 5% by mass or less, relative to 100% by mass of the epoxy resin composition.

[0038] (Other ingredients) Other components that may be further contained in component (B) include various optional additives. In the case of particles, the additives are different from component (C) or component (C2), and examples include thermoplastic resins, elastomer fine particles, core-shell elastomer fine particles, diluents, inorganic particles (e.g., silica), carbonaceous components (e.g., carbon nanotubes), flame retardants (e.g., phosphorus compounds), and defoamers. From the viewpoints of improving the toughness of the cured product of component (B) without reducing its heat resistance, adjusting the viscosity of the epoxy resin composition, and preventing a large amount of the epoxy resin composition from flowing out of the prepreg during molding, the additive is preferably either a thermoplastic resin or core-shell elastomer fine particles.

[0039] Examples of the thermoplastic resin include polyethersulfone, polyvinyl formal, phenoxy resin, and acrylic block copolymer. Commercially available polyethersulfone products include, for example, ULTRASON (registered trademark) E2020 P SR MICRO from BASF, Sumikaexcel PES 5003P from Sumitomo Chemical, and Virantage (registered trademark) VW-10200RP and VW-10700RP from Solvay. Commercially available polyvinyl formal products include, for example, Vinylec from JNC. Commercially available phenoxy resins include, for example, Phenototo from Nippon Steel Chemical & Material, and PKHB, PKHC, and PKHH from InChem. Commercially available acrylic block copolymers include, for example, the NANOSTRENGTH (registered trademark) series, such as Arkema's NANOSTRENGTH (registered trademark) M52N and M22. While the component (C) has a particle shape in the epoxy resin composition, these thermoplastic resins as other components (excluding the component (C)) are preferably dissolved in the epoxy resin in the epoxy resin composition to form a homogeneous state.

[0040] (Method for preparing component (B)) The component (B) can be prepared by any of a variety of methods, including, for example, a method in which the components of the epoxy resin composition are heated and kneaded in a planetary mixer, kneader, or the like.

[0041] The curing agent, such as dicyandiamide or an aromatic urea compound, is a particulate component that may aggregate and result in poor dispersion. Therefore, it is preferable to premix the particulate component with a liquid epoxy resin to form a masterbatch. For the premixing, it is preferable to use a kneading device such as a three-roll mill or a ball mill. For example, by preparing a particulate curing agent as a masterbatch in advance, it is possible to prevent uneven physical properties in the cured product of component (B), poor curing, and poor impregnation of component (B) into component (A) due to poor dispersion of the curing agent. From the viewpoint of reducing fracture origins resulting from uniform dispersion of solids, the mass ratio of the content of the curing agent to the content of component (C) or component (C2) (curing agent / component (C) or component (C2)) is preferably 0.1 or more, more preferably 0.25 or more. Furthermore, it is preferably 0.5 or less, more preferably 0.4 or less.

[0042] (Component (C), component (C2)) The component (C) is a particle. The particle may be an inorganic particle or an organic particle. The shape of the particle is not particularly limited, and may be a sphere, a spheroid, a triangular prism, a rectangular parallelepiped, a cone, or the like. Examples of inorganic particles include silica, carbon black, metal oxides, and metal hydroxides. Examples of organic particles that can be used include thermoplastic resin particles and thermosetting resin particles. The component (C2) is a polymer having a glass transition temperature of 10°C or lower as observed under the above measurement conditions. From the viewpoint of toughness, the component (C2) is preferably in the form of particles. The components (C) and (C2) are preferably thermoplastic resin particles. From the viewpoint of impact resistance when a fiber-reinforced composite material is formed, it is preferable that 60% by mass or more of the total amount of the component (C) or the component (C2) is present on the surface of the prepreg, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. Some of the component (C) or the component (C2) penetrates into the layer composed of the component (A). For this reason, the component (C) or the component (C2) present on the surface of the prepreg is 100% by mass or less of the total amount of the component (C) or the component (C2).

[0043] Examples of thermoplastic resin particles include polyamide, polyurethane, polyethersulfone, polyvinyl formal, phenoxy resin, polymethacrylate, polyacrylate, acrylic block copolymer, etc. Among these, polyacrylate is preferred from the viewpoint of excellent impact resistance. Examples of polyacrylic acid esters include polymethyl acrylate, polybutyl acrylate, polypentyl acrylate, and polyhexyl acrylate. Commercially available polyacrylic acid esters include ARX15, ARX30, ABX8, ABX20, AFX8, AFX15, and AFX30 (manufactured by Sekisui Plastics Co., Ltd.). Among these, crosslinked polyacrylic acid esters are preferred from the viewpoints of resistance to point impact and solvent resistance. The crosslinked polyacrylic acid esters are those in which the ester structural moieties of the side chains are chemically bonded to each other, and when heated, they exceed the glass transition temperature and pass through a rubbery state, after which they do not become fluid.

[0044] (Glass transition temperatures of components (C) and (C2)) The glass transition temperatures of the constituent elements (C) and (C2) are preferably 0°C or lower, more preferably -10°C or lower, and even more preferably -20°C or lower. The constituent elements (C) and (C2) are preferably in a rubbery state in the temperature range in which the fiber-reinforced composite material is used (for example, a range of -15°C to 40°C determined depending on the application). From the viewpoint of being able to exist as solid particles at room temperature, a temperature of -80°C or higher is preferred. When the glass transition temperature is 10°C or lower, there is no significant change in the modulus of elasticity in normal use environments, and there is little change in impact resistance depending on the use environment. Furthermore, when the glass transition temperature is 40°C or higher, the particles are in a glassy state in normal use environments. To identify component (C) or component (C2) in the prepreg, cut a piece of prepreg into a 100 mm x 100 mm piece, wash it with 50 ml of NMP (N-methylpyrrolidone), and then filter the washings through filter paper. This process is repeated five times using the same filter paper, then wash the filter paper with acetone and dry it in an oven at 100°C for 30 minutes. It is preferable to extract 5 to 10 mg of residue from the filter paper and scan it by differential scanning calorimetry (DSC) from -50°C to 300°C at 10°C / min to determine the glass transition temperature in accordance with JIS K7121.

[0045] (Particle size distribution) The particle size distribution of component (C) or component (C2) is preferably such that D25 is 7 to 15 μm, median (D50) is 12 to 21 μm, and D75 is 15 to 23 μm. When D25 of component (C) or component (C2) is within the range of 7 to 15 μm, component (C) is less likely to penetrate into component (A) during the production of prepregs and fiber-reinforced composite materials. Therefore, component (C) or component (C2) can be frequently present between layers of component (A). As a result, excellent impact resistance can be imparted to fiber-reinforced composite materials. When D75 of component (C) or component (C2) is within the range of 15 to 23 μm, deterioration in the mechanical properties of fiber-reinforced composite materials can be suppressed. Furthermore, when a mixture of component (B) and component (C) or component (C2) is applied to the surface of release paper in a uniform thickness during the production of prepregs, clogging can be suppressed in equipment such as roll coaters and die coaters. If the median (D50) and mode are 12 to 21 μm, the particles can absorb the energy generated by impact and break down, thereby enhancing the effect of preventing cracks from spreading. The particle size distribution of the component (C) or the component (C2) can be obtained, for example, by a laser diffraction / scattering method.

[0046] Prepreg fiber weight (1m 2 The content of reinforcing fibers per unit area (FAW) may be appropriately set depending on the application of the prepreg, for example, 50 to 250 g / m 2 is.

[0047] The content of the matrix resin in the prepreg is the sum of the content of the component (B) and the content of the component (C) or the component (C2). The content of the matrix resin in the prepreg is preferably 25% by mass or more, more preferably 30% by mass or more, and preferably 50% by mass or less, more preferably 45% by mass or less, based on 100% by mass of the prepreg. When the content of the matrix resin in the prepreg is equal to or greater than the lower limit of the above range, sufficient impact resistance can be imparted. Furthermore, deterioration in the static mechanical properties of the fiber-reinforced composite material due to a shortage of the component (B) in the fiber-reinforced composite material can be suppressed. When the content of the matrix resin in the prepreg is equal to or less than the upper limit of the above range, deterioration in the static mechanical properties of the fiber-reinforced composite material due to a decrease in Vf (the volume fraction of the reinforcing fiber substrate in the fiber-reinforced composite material) caused by an excessive content of the component (B) and the component (C) or the component (C2) can be prevented.

[0048] The content of component (C) or component (C2) in the prepreg is preferably 5% by mass or more, more preferably 10% by mass or more, based on 100% by mass of the total of component (B) and component (C) or component (C2). Furthermore, the content of component (C) or component (C2) in the prepreg is preferably 30% by mass or less, more preferably 25% by mass or less, based on 100% by mass of the total of component (B) and component (C) or component (C2). When the content of component (C) or component (C2) is equal to or greater than the lower limit of the above range, the amount of component (C) or component (C2) unevenly distributed in the interlaminar region increases, thereby further improving impact resistance. When the content of component (C) is equal to or less than the upper limit of the above range, the proportion of component (B) in the matrix resin composed of component (B) and component (C) or component (C2) contained in the prepreg can be prevented from becoming too low, and a decrease in the static mechanical strength of the fiber-reinforced composite material due to a shortage of component (B) can be prevented.

[0049] (Prepreg manufacturing method) As a method for producing a prepreg, the method (α) described below is preferred because it is easy to unevenly distribute the component (C) or the component (C2) in an interlayer region formed between the components (A) and because the same method as that for producing a general prepreg can be employed and there is no increase in production costs.

[0050] Method (α) is a method in which a resin film (D) is prepared by thinly spreading a mixture (BC) obtained by kneading component (C) or component (C2) into component (B) using a film coater, and the resulting resin film (D) is laminated to one or both surfaces of component (A), and component (A) is impregnated with component (B). In method (α), when component (B) is impregnated into component (A), component (C) is filtered out by component (A) and is unevenly distributed near the surface of the prepreg.

[0051] (heat molding) The temperature during thermoforming of the laminated prepregs is preferably 100°C or higher, more preferably 110°C or higher, and preferably 150°C or lower, more preferably 140°C or lower, from the viewpoints of the performance of the thermoforming equipment, the properties of the auxiliary materials, and the properties of the resulting fiber-reinforced composite material. When the thermoforming temperature is 100°C or higher, component (B) can be sufficiently cured, resulting in a fiber-reinforced composite material with high heat resistance. When the thermoforming temperature is 150°C or lower, an oven with general specifications can be used, and steam can be used as the heat medium. Furthermore, from the viewpoint of maintaining the performance of the resulting fiber-reinforced composite material, the rapid progress of the curing reaction can prevent excessive reaction heat from being generated in a short period of time, which would otherwise burn the interior of the fiber-reinforced composite material. Examples of molding methods include autoclave molding, sheet winding molding, press molding, and internal pressure molding. Prepregs of the aforementioned embodiments may be laminated together, or a prepreg not having component (C) or component (C2) may be laminated onto a prepreg of the aforementioned embodiment.

[0052] <Fiber-reinforced composite materials> A fiber-reinforced composite material according to one embodiment of the present invention is a fiber-reinforced composite material obtained by laminating two or more prepregs and heat-curing them. Furthermore, in the cross section of the fiber-reinforced composite material, layers with uneven particle distribution exist between the fiber layers. In the layer with uneven particle distribution, the cross-sectional shape of the particles may be circular or elliptical, or may be irregular. Examples of components using the fiber-reinforced composite material include flat plates and hollow components. Examples of flat plates include flat plates with curved or uneven shapes (automobile roofs, hat channels), etc. Examples of hollow components include hollow components with curved portions (rackets, bicycle wheels), cylindrical tubular bodies (golf shafts, fishing rods, bats), and tubular bodies with polygonal cross sections (bicycle frames).

[0053] As other examples of embodiments, the following <1> to <11> are further disclosed in this specification, but the present invention is not limited to these embodiments. <1> A prepreg comprising the following components (A), (B), and (C), wherein the component (C) is present in a surface layer of the prepreg, and the prepreg is cured under the following curing conditions, and the projected area of ​​a damaged portion of a cured product measured by the following test 1 is 400 mm 2 or less, and the maximum value of tan δ of the cured product measured by the following Test 2 is observed at 100°C or higher. Component (A): Reinforced fiber substrate Component (B): Epoxy resin composition Component (C): Particle Curing conditions: The prepreg is laminated in a "+45 / 0 / -45 / 90" 4s configuration and cured in an autoclave at 0.6 MPa and 150°C for 30 minutes. Test 1: The hardened panel is placed at rest, and an iron impactor with a tip diameter of 16 mm and R=8 mm is dropped onto the center of the panel with a potential energy of 26 J. The damaged area is detected using a transmission type ultrasonic flaw detector at a sound pressure of 22 dB, and the area of ​​the detected damaged area is measured. Test 2: Using a dynamic viscoelasticity measuring device, measure the storage modulus E' and loss modulus E'' under the conditions of a frequency of 1 Hz, a heating rate of 5°C / min, and a measurement temperature range of 30°C to 250°C. Observe the temperature at which the ratio of storage modulus E' to loss modulus E'' (E'' / E' = tan δ) is maximized. <2> The prepreg according to <1>, wherein the component (C) is thermoplastic resin particles. <3> The prepreg according to <1> or <2>, wherein the component (C) is a particle containing a polyacrylic acid ester. <4> The prepreg according to any one of <1> to <3>, wherein the component (C) is crosslinked particles of a polyacrylic acid ester. <5> The prepreg according to any one of <1> to <4>, wherein the median (D50) of the particle size distribution of the particles of the component (C) is 12 μm or more and 21 μm or less. <6> The prepreg according to any one of <1> to <5>, wherein the component (B) contains dicyandiamide. <7> The prepreg according to any one of <1> to <6>, wherein the component (B) contains an epoxy resin having a glass transition temperature of −20° C. or lower as a cured product. <8> The prepreg according to any one of <1> to <7>, wherein the component (A) is a carbon fiber substrate. <9> A fiber-reinforced composite material obtained by laminating at least one sheet of the prepreg according to any one of <1> to <8> and another prepreg. <10> A prepreg comprising the following components (A), (B), and (C3), wherein the component (C3) is present in a surface layer of the prepreg: Component (A): Reinforced fiber substrate Component (B): Epoxy resin composition Component (C3): Polyacrylate particles <11> A prepreg comprising the following components (A), (B), and (C4), wherein the component (C4) is present in a surface layer of the prepreg: Component (A): Reinforced fiber substrate Component (B): Epoxy resin composition Component (C4): Crosslinked particles [Example]

[0054] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.

[0055] <Raw materials> The raw materials used in Examples 1 to 3 and Comparative Examples 1 to 6 are as follows.

[0056] (Component (A)) TR50S: Carbon fiber bundle (Mitsubishi Chemical, PYROFIL (registered trademark) TR50S 15L, strand strength: 4900 MPa, elastic modulus: 240 GPa, carbon fiber diameter: 6.8 μm, number of carbon fibers: 15,000)

[0057] (Component (B)) [Epoxy resin] YD-128: Bisphenol A liquid epoxy resin (Nippon Steel Chemical & Material) jER1002: Bisphenol A solid epoxy resin (Mitsubishi Chemical) YDPN-638: Phenol novolac semi-solid epoxy resin (Nippon Steel Chemical & Material) YD-952: Epoxy resin with an oxazolidone ring structure (Nippon Steel Chemical & Material) YX7400: Liquid bifunctional epoxy resin (Mitsubishi Chemical) [Hardening agent] DICY15: Dicyandiamide (Mitsubishi Chemical jER Cure (registered trademark) DICY15) DCMU99: 3-(3,4-dichlorophenyl)-1,1-dimethylurea (Hodogaya Chemical Co., Ltd., DCMU99) Omicure 94: Phenyldimethylurea (PTI Japan) 2MZA-PW: 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine (Shikoku Chemicals Corporation)

[0058] (Component (C)) ARX15: Cross-linked polyacrylic ester (Sekisui Chemical Co., Ltd., glass transition temperature -26°C, median particle size distribution (D50): 15 μm) ARX30: Cross-linked polyacrylic ester (Sekisui Chemical Co., Ltd., glass transition temperature -26°C, median particle size distribution (D50): 30 μm)

[0059] (Particles other than component (C)) BM30X-12: Cross-linked polybutyl methacrylate (Sekisui Chemical Co., Ltd., median particle size distribution (D50): 12 μm) MBX15: Cross-linked polymethyl methacrylate (Sekisui Chemical Co., Ltd., glass transition temperature 75°C, median particle size distribution (D50): 15 μm) 2A P0-35: Copolymer polyamide particles (Ms Chemie Japan, glass transition temperature: 15°C, median particle size distribution (D50): 27 μm)

[0060] (Other ingredients) Vinylec E: Polyvinyl formal (JNC) PES5003P: Polyethersulfone (Sumitomo Chemical)

[0061] Example 1 (Preparation of component (B)) To prepare raw material composition 1a (also referred to as masterbatch) for component (B), 49 parts by mass of YD-128, 24 parts by mass of jER1002, 25 parts by mass of YD-952, and 2.5 parts by mass of Vinylec E were added to a glass flask. Using an oil bath set at 140-160°C, raw material composition 1a was heated and mixed until homogeneous. Meanwhile, to prepare raw material composition 1b for component (B), 12 parts by mass of YD-128, 6 parts by mass of DICY15, and 4 parts by mass of DCMU99 were added to the container of a planetary centrifugal mixer, and raw material composition 1b was stirred and degassed. Furthermore, the DICY15 and DCMU99 in raw material composition 1b were uniformly dispersed in YD-128 using a roll mill. 100.5 parts by mass of raw material composition 1a in a glass flask that had been allowed to cool to a temperature of about 60°C and 22 parts by mass of the above-mentioned raw material composition 1b were added to the container of a planetary mixer, and the jacket temperature was set to 60 to 65°C. The components were mixed until homogeneous, thereby preparing component (B).

[0062] (Preparation of Mixture (BC)) To 122.5 parts by mass of the prepared component (B), 35 parts by mass of ARX15 were added. Therefore, the content of ARX15 was 22.2% by mass relative to 100% by mass of the total of component (B) and component (C). The jacket temperature of the planetary mixer was set to 60 to 70°C, and the components were mixed until homogeneous, thereby preparing a mixture (BC) of component (B) and component (C).

[0063] (Prepreg production) The prepreg of Example 1 was produced by the method (α) disclosed in the embodiment. The mixture (BC) was applied to the surface of the release paper with a film coater at a uniform thickness of 32 g / m 2A resin film (F) of the above was produced. The produced resin film (F) was attached to both sides of a sheet-shaped component (A) made by aligning multiple TR50S strands, and the component (A) was impregnated with component (B) by heating and pressing at 100°C, thereby producing a prepreg. At this time, in the prepreg, component (C) contained in component (B) was filtered out by component (A), and was unevenly distributed near the surface of the prepreg.

[0064] (Manufacturing of fiber-reinforced composite materials) The resulting prepreg was cut into 350mm x 350mm pieces using an automatic cutting device and laminated in a "+45 / 0 / -45 / 90" 4s configuration to produce a prepreg laminate. The prepreg laminate was covered with a vacuum bag and subjected to vacuum bag treatment. It was then heated to 150°C at a heating rate of 4°C / min using an autoclave and maintained at 150°C for 20 minutes. The prepreg laminate was then slowly cooled in the autoclave to 50°C or below to produce a molded plate for evaluation. The pressure inside the autoclave was 0.6 MPa from the start to the end of heating.

[0065] (Measurement of glass transition temperature) Test specimens measuring 55 mm in length and 12.5 mm in width were cut from the molded plates for evaluation. The storage modulus E' and loss modulus E'' were measured in bending mode using a dynamic viscoelasticity measuring device (TA Instruments, "DMA-Q800") in accordance with ASTM D7028 under the following conditions: frequency: 1 Hz, heating rate: 5°C / min, and measurement temperature range: 30°C to 250°C. The maximum value of the ratio of storage modulus E' to loss modulus E'' (E'' / E' = tan δ) was taken as the glass transition temperature.

[0066] (Impact resistance test) A 150mm x 100mm test piece was cut out from the evaluation molded plate and placed in an instrumented impact testing machine. An iron impactor with a hemisphere of 8mm radius attached to the tip was set to a potential energy of 26J and dropped onto the center of the test piece. Ultrasonic waves of 22dB were irradiated onto the test piece to detect damaged areas. The damaged area was projected and the projected area S was measured. The absorbed energy E was taken as the area enclosed by the load-displacement curve.

[0067] <Example 2> (Preparation of component (B)) To prepare raw material composition 2a for component (B), 38 parts by mass of YD-128, 5 parts by mass of YX7400, 27 parts by mass of jER1002, 28 parts by mass of YD-952, and 2.8 parts by mass of Vinylec E were added to a glass flask. Using an oil bath set at a temperature of 140 to 160°C, the ingredients were mixed while heating until raw material composition 2a became uniform.

[0068] Raw material composition 2b of component (B) was obtained using the same procedure and formulation as for 1b in Example 1. 100.8 parts by mass of raw material composition 2a in a glass flask that had been allowed to cool to a temperature of about 60°C and 22 parts by mass of the above-mentioned raw material composition 2b were added to the container of a planetary mixer, and the jacket temperature was set to 60 to 65°C, and the components were mixed until uniform, thereby obtaining component (B) used in Example 2.

[0069] (Preparation of Mixture (BC)) 35 parts by mass of ARX15 were added to 122.8 parts by mass of the prepared component (B). Therefore, the content of ARX15 was 22.2% by mass relative to 100% by mass of the total of component (B) and component (C). The jacket temperature of the planetary mixer was set to 60 to 70°C, and the components were mixed until homogeneous, thereby preparing a mixture (BC) of component (B) and component (C).

[0070] (Prepreg production) Except for changing the mixture (BC), the prepreg used in Example 2 was produced by the same method (α) as in Example 1. The composition and production method of the prepreg are shown in Table 1.

[0071] (Manufacturing of fiber-reinforced composite materials) A molded plate for evaluation of Example 2 was produced in the same manner as in Example 1. The molded plate for evaluation of Example 2 was evaluated, and the results are shown in Table 1.

[0072] Example 3 (Preparation of component (B)) The component (B) used in Example 3 was obtained using the same procedure and formulation as in Example 1.

[0073] (Preparation of Mixture (BC)) 35 parts by mass of ARX30 were added to 122.5 parts by mass of the prepared component (B). Therefore, the content of ARX30 was 22.2% by mass relative to 100% by mass of the total of component (B) and component (C). The jacket temperature of the planetary mixer was set to 60 to 70°C, and the components were mixed until homogeneous, thereby preparing a mixture (BC) of component (B) and component (C).

[0074] (Prepreg production) Except for changing the mixture (BC), the prepreg used in Example 3 was produced by the same method (α) as in Example 1. The composition and production method of the prepreg are shown in Table 1.

[0075] (Manufacturing of fiber-reinforced composite materials) A molded plate for evaluation of Example 3 was produced in the same manner as in Example 1. The molded plate for evaluation of Example 3 was evaluated, and the results are shown in Table 1.

[0076] <Comparative Example 1> (Preparation of component (B)) To prepare raw material composition 3a for component (B), 49 parts by mass of YD-128, 24 parts by mass of jER1002, 25 parts by mass of YD-952, and 2.5 parts by mass of Vinylec E were added to a glass flask. Using an oil bath set at a temperature of 140 to 160°C, the raw materials were mixed while heating until they became uniform. On the other hand, to prepare raw material composition 3b for component (B), 12 parts by mass of YD-128, 6 parts by mass of DICY15, and 4 parts by mass of DCMU99 were added to the container of a planetary mixer, and raw material composition 4b was stirred and degassed. Furthermore, the DICY15 and DCMU99 in raw material composition 3b were uniformly dispersed in the YD-128 using a roll mill. 100.5 parts by mass of raw material composition 3a in a glass flask that had been allowed to cool to about 60°C and 22 parts by mass of the above-mentioned raw material composition 3b were added to the container of a planetary mixer, and the jacket temperature was set to 60 to 65°C. The components were mixed until uniform, thereby preparing component (B) used in Comparative Example 1.

[0077] (Preparation of Mixture (BC)) 35 parts by mass of BM30X-12 were added to 122.5 parts by mass of the prepared component (B). Therefore, the content of BM30X-12 was 22.2% by mass relative to 100% by mass of the total of component (B) and component (C). The jacket temperature of the planetary mixer was set to 60 to 70°C, and the components were mixed until homogeneous, thereby preparing a mixture (BC) of component (B) and component (C).

[0078] (Prepreg production) The obtained mixture (BC) was subjected to the same method (α) as in Example 1 to prepare a prepreg to be used in Comparative Example 1.

[0079] (Manufacturing of fiber-reinforced composite materials) A molded plate for evaluation of Comparative Example 1 was produced in the same manner as in Example 1. Evaluation was carried out on the molded plate for evaluation of Comparative Example 1. The results are shown in Table 1.

[0080] <Comparative Example 2> (Preparation of component (B)) Constituent element (B) was prepared in the same manner as in Example 2.

[0081] (Preparation of Mixture (BC)) To 122.5 parts by mass of the prepared component (B), 35 parts by mass of MBX15 were added. Therefore, the content of MBX15 was 22.2% by mass relative to the total of 100% by mass of component (B) and component (C). The jacket temperature of the planetary mixer was set to 60 to 70°C, and the components were mixed until homogeneous, thereby preparing a mixture (BC) of component (B) and component (C).

[0082] (Prepreg production) The prepreg used in Comparative Example 2 was produced by the same method (α) as in Comparative Example 1.

[0083] (Manufacturing of fiber-reinforced composite materials) A molded plate for evaluation of Comparative Example 2 was produced in the same manner as in Example 1. Evaluation was carried out on the molded plate for evaluation of Comparative Example 2. The results are shown in Table 1.

[0084] <Comparative Example 3> (Preparation of component (B)) Constituent element (B) was prepared in the same manner as in Comparative Example 1.

[0085] (Preparation of Mixture (BC)) To 122.5 parts by mass of the prepared component (B), 35 parts by mass of 2A P0-35 were added. Therefore, the content of 2A P0-35 was 22.2% by mass relative to 100% by mass of the total of component (B) and component (C). The jacket temperature of the planetary mixer was set to 60 to 70°C, and the components were mixed until homogeneous, thereby preparing a mixture (BC) of component (B) and component (C).

[0086] (Prepreg production) The prepreg used in Comparative Example 3 was produced by the same method (α) as in Comparative Example 1.

[0087] (Manufacturing of fiber-reinforced composite materials) A molded plate for evaluation of Comparative Example 3 was produced in the same manner as in Example 1. The molded plate for evaluation of Comparative Example 3 was evaluated, and the results are shown in Table 1.

[0088] <Comparative Example 4> (Preparation of component (B)) To prepare raw material composition 4a for component (B), 41 parts by mass of YD-128, 29 parts by mass of jER1002, 30 parts by mass of YD-952, and 3 parts by mass of Vinylec E were added to a glass flask. Using an oil bath set at a temperature of 140 to 160°C, the raw materials were mixed while heating until they became homogeneous. On the other hand, to prepare raw material composition 4b for component (B), 12 parts by mass of YD-128, 6 parts by mass of DICY15, and 4 parts by mass of DCMU99 were added to the container of a planetary mixer, and raw material composition 4b was stirred. Furthermore, the DICY15 and DCMU99 in raw material composition 4b were uniformly dispersed in YD-128 using a roll mill. 103 parts by mass of raw material composition 4a in a glass flask that had been allowed to cool to about 60°C and 22 parts by mass of the above-mentioned raw material composition 4b were added to the container of a planetary mixer, and the jacket temperature was set to 60 to 65°C. The components were mixed until uniform, thereby preparing component (B) used in Comparative Example 1.

[0089] (Prepreg production) A prepreg used in Comparative Example 4 was produced by the same method (α) as in Comparative Example 1 using only the component (B).

[0090] (Manufacturing of fiber-reinforced composite materials) A molded plate for evaluation of Comparative Example 4 was produced in the same manner as in Example 1. The molded plate for evaluation of Comparative Example 4 was evaluated, and the results are shown in Table 1.

[0091] <Comparative Example 5> A component (B) was obtained in the same manner as in Comparative Example 4, except that the raw materials and their blending ratios were changed as shown in Table 1.

[0092] (Prepreg production) A prepreg used in Comparative Example 5 was produced by the same method (α) as in Comparative Example 1 using only the component (B).

[0093] (Manufacturing of fiber-reinforced composite materials) A molded plate for evaluation of Comparative Example 5 was produced in the same manner as in Example 1. The molded plate for evaluation of Comparative Example 5 was evaluated, and the results are shown in Table 1.

[0094] <Comparative Example 6> A component (B) was obtained in the same manner as in Comparative Example 4, except that the raw materials and their blending ratios were changed as shown in Table 1.

[0095] (Prepreg production) A prepreg used in Comparative Example 6 was produced by the same method (α) as in Comparative Example 1 using only the component (B).

[0096] (Manufacturing of fiber-reinforced composite materials) A molded plate for evaluation of Comparative Example 6 was produced in the same manner as in Example 1. The molded plate for evaluation of Comparative Example 6 was evaluated, and the results are shown in Table 1.

[0097] [Table 1]

[0098] The fiber-reinforced composite materials of Examples 1 to 3, which contained the component (C) and most of which was present between layers of the component (A), all had heat resistance of 100°C or higher and excellent impact resistance. On the other hand, the fiber-reinforced composite materials of Comparative Examples 1 to 6, which did not contain the component (C), all had poor impact resistance or poor heat resistance. [Industrial Applicability]

[0099] The prepreg of the present invention provides a fiber-reinforced composite material in which delamination between layers upon point impact is suppressed. The fiber-reinforced composite material of the present invention has excellent resistance to point impact. According to the method for producing a fiber-reinforced composite material of the present invention, a fiber-reinforced composite material having excellent resistance to point impact can be obtained.

Claims

1. A prepreg, The prepreg includes the following components (A), (B), and (C): The prepreg is cured under the following curing conditions to obtain a cured product having a projected area of ​​a damaged portion of 400 mm2 or less, as measured by the following test 1: 2 is as follows: A prepreg, wherein the maximum value of tan δ of the cured product, as measured by the following Test 2, is observed at 100° C. or higher. Component (A): Reinforced fiber substrate Component (B): Epoxy resin composition Component (C): Particles which are crosslinked particles of polyacrylic ester and have a glass transition temperature of 10° C. or lower as measured under the following measurement conditions: Curing conditions: The prepregs were laminated in a configuration of "+45 / 0 / -45 / 90" 4s, and cured in an autoclave at 0.6 MPa and 150°C for 30 minutes. Test 1: A panel made of the cured product was placed, and an iron impactor with a hemisphere of radius 8 mm at its tip was dropped onto the center of the panel with a potential energy of 26 J. Damage on the panel caused by the drop was detected with a through-beam ultrasonic flaw detector at a sound pressure of 22 dB, and the area of ​​the detected damage was measured and regarded as the projected area of ​​the damage. Test 2: Using a dynamic viscoelasticity measuring device, the storage modulus E' and the loss modulus E'' are measured under conditions of a frequency of 1 Hz, a heating rate of 5°C / min, and a measurement temperature range of 30°C to 250°C, and the ratio of the loss modulus E'' to the storage modulus E' (E'' / E') is defined as tan δ. Measurement conditions for the glass transition temperature of the component (C): The prepreg is cut to 100 mm x 100 mm, washed with 50 ml of NMP (N-methylpyrrolidone), and the washing liquid is filtered through filter paper. This process is repeated five times with the same filter paper, and the filter paper is washed with acetone and dried in an oven at 100°C for 30 minutes. 5 to 10 mg of residue is taken out from the filter paper, and scanned from -50°C to 300°C at 10°C / min by differential scanning calorimetry (DSC), and the onset value at which the baseline changes is taken as the glass transition point.

2. The prepreg according to claim 1 , wherein the component (C) is present on an outermost surface of the prepreg.

3. 3. The prepreg according to claim 1 or 2, wherein the median (D50) of the particle size distribution of the particles of the component (C) is 12 μm or more and 21 μm or less.

4. The prepreg according to any one of claims 1 to 3, wherein the component (B) contains dicyandiamide.

5. The prepreg according to any one of claims 1 to 4, wherein the component (B) contains an epoxy resin, and a glass transition temperature of a cured product of the epoxy resin is -20°C or lower.

6. The prepreg according to any one of claims 1 to 5, wherein the component (A) is a carbon fiber substrate.

7. A fiber-reinforced composite material obtained by laminating at least one sheet of the prepreg according to any one of claims 1 to 6 and another prepreg.

8. The composition includes the following components (A), (B), and (C2), The component (C2) is present on an outermost surface of the prepreg. Component (A): Reinforced fiber substrate Component (B): Epoxy resin composition Component (C2): Particles which are crosslinked particles of polyacrylic ester and have a glass transition temperature of 10° C. or lower as measured under the following measurement conditions: Measurement conditions for the glass transition temperature of the component (C2): The prepreg is cut to 100 mm x 100 mm, washed with 50 ml of NMP (N-methylpyrrolidone), and the washing liquid is filtered through filter paper. This process is repeated five times with the same filter paper, and the filter paper is washed with acetone and dried in an oven at 100°C for 30 minutes. 5 to 10 mg of residue is taken out from the filter paper, and scanned from -50°C to 300°C at 10°C / min by differential scanning calorimetry (DSC), and the onset value at which the baseline changes is taken as the glass transition point.

9. The prepreg according to claim 8, wherein the component (C2) is unevenly distributed on an outermost surface of the prepreg.

10. The prepreg according to claim 8 or 9, wherein the component (A) is a carbon fiber substrate.

11. The prepreg according to any one of claims 8 to 10, which is for a tubular body.

12. A tubular body obtained by curing the prepreg according to any one of claims 8 to 11.

13. A method for producing a fiber-reinforced composite material, comprising hot-molding a prepreg containing the following components (A), (B), and (C2) at 100° C. or higher and 150° C. or lower: Component (A): Reinforced fiber substrate Component (B): Epoxy resin Component (C2): A crosslinked polyacrylic acid ester polymer having a glass transition temperature of 10° C. or less as measured under the following measurement conditions. Measurement conditions for the glass transition temperature of the component (C2): The prepreg is cut to 100 mm x 100 mm, washed with 50 ml of NMP (N-methylpyrrolidone), and the washing liquid is filtered through filter paper. This process is repeated five times with the same filter paper, and the filter paper is washed with acetone and dried in an oven at 100°C for 30 minutes. 5 to 10 mg of residue is taken out from the filter paper, and scanned from -50°C to 300°C at 10°C / min by differential scanning calorimetry (DSC), and the onset value at which the baseline changes is taken as the glass transition point.

14. The method for producing a fiber-reinforced composite material according to claim 13, wherein the prepreg is molded by internal pressure molding, autoclave molding, or press molding.

Citation Information

Patent Citations

  • Epoxy resin composition for low-temperature curing type prepreg and prepreg using the same

    JP1995196769A

  • Epoxy resin composition for fiber reinforced composite material, prepreg and fiber reinforced composite material

    JP1997025393A

  • Prepreg and fiber reinforced composite material

    JP2014145003A

  • Production method of thermosetting resin composition and use of the same

    JP2017206591A

  • Prepreg, fiber-reinforced composite material, and method for producing prepreg

    WO2011122631A1